A psychobiographical study of Charlize Theron - Prenter, Tracey (Rhodes University, Faculty of Humanities, Department of Psychology, 2016)
Psychobiographers study the lives of extraordinary, prominent, and enigmatic individuals. Psychobiographical research advances our insight into the uniqueness and complexity of the human personality and therefore makes a substantial contribution towards one of the major objectives of the field of psychology. Purposive sampling was employed to select Charlize Theron as the subject of this psychobiographical study. As the only South African who has won an Oscar, Theron is an exceptional individual who demonstrates tenacity and a will to succeed despite significant traumatic events in her childhood. The case study data was organised and analysed according to the general analytic approach developed by Huberman and Miles (2002) and one of Alexander's (1990) strategies, namely questioning the data. Erikson's psychosocial theory (1950, 1963, 1995) was selected to guide this study because it recognises the impact of socio-cultural influences on developmental processes and provides a comprehensive, staged framework for studying Theron's personality development. This study contributes to the development of psychobiographical research in South Africa.
Keywords: Theron, Charlize -- Psychology; Motion picture actors and actresses -- South Africa -- Biography; Motion picture actors and actresses -- United States -- Biography; Psychology -- Biographical methods